Research frameworks and Paradigms in Female entrepreneurship: Female and Integrative Perspectives - Nouh, Kheiri; Fouzi djamel eddine, Haouari; Mohamed Sabir, Gacem (International Journal of Psychosocial Rehabilitation, 2022)
This study aims to provide a theoretical framework that stems from deconstructing the concept of entrepreneurship from its broad perspective, allocating the perspectives that practiced research in entrepreneurship on the basis of gender, and contributed to creating a unique academic discourse with its ideological approaches and orientations, and its objectives related to entrepreneurship as a free development act, as well as to women. As an agent within the limits of her social context.This study, through the practice of in-depth review of the specialized literature, presented the research frameworks and methodological premises from which women's entrepreneurship started at as a special topic in the academic discourse, which led to a multiplicity of perspectives and consequently a multiplicity of paradigms that practiced understanding both from its epistemic and ideological angles. The study concluded to present an epistemological analysis of these academic discourses by extracting the most important axioms from which a deeper understanding can be achieved beyond simple reading.